Structure-property insights into chiral thiophene copolymers by direct heteroarylation polymerization - Nikam, Shrikant B.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Asha, S. K. (European Polymer Journal, 2022)
Chiral thiophene copolymers with fluorene as co monomer are designed having N-Boc-L-glutamic acid-1-tert-butyl ester as a chiral substituent located either on the thiophene unit or the fluorene unit with varying spacer length. The atom-economic direct heteroarylation polymerization (DHAP) method is utilized for the polymerization. Gibb's free energy (delta G) for polymerization determined using DFT calculations indicate difficulty in achieving high molar mass when the bulky chiral substituents are attached through short spacer to the backbone. The experimental observations are in agreement with the theoretical calculations with no polymer-ization or very low molar mass sticky compounds obtained for reactions with predicted + & UDelta;G values. Structure -property relationship are compared for two chiral polymers -P4 and P5 having the chiral substitution on thiophene and fluorene units respectively. No CD signal is observed in THF-a good solvent where the polymers are molecularly dissolved. Intense bisignated CD signal is observed for both polymers upon addition of methanol - a poor solvent, to their THF solution. The bisignate CD signal with maxima at lower wavelength and inflection point associated with the pi-pi* absorption band is characteristic of exciton coupling between polymer chains in a left handed helical orientation. Small differences are observed in the intensity of the CD signal for the polymers P4 and P5 highlighting the impact of steric hindrance of bulky pendant groups on polymer conformation. DHAP is an atom economic polymerization procedure that can be gainfully utilized for developing chiral conjugated polymers.
Keywords: chiral; DFT; Direct heteroarylation polymerization; Gibb?s free energy; Steric Hindrance